Gender Bias Interacts With Instructor Disfluency to Negatively Affect Student Evaluations of Teaching - LaPaglia, Jessica; Miller, Katelyn; Protexter, Samantha (Frontiers in Education, 2022)
Recent research has shown that instructor fluency can impact student judgments of learning and instructor ratings but has no real effect on actual learning. In addition, women tend to receive lower course and instructor evaluations than men. In the current study, we examined how instructor fluency and instructor gender influenced instructor evaluations and student learning. Participants watched a short lecture video. The speaker was either male or female and was either fluent (i.e., even paced in their speech) or disfluent (i.e., disorganized, made mistakes). Following the video, participants evaluated the instructor and took a quiz over the lecture. Results indicated that disfluency negatively affected quiz scores, but instructor gender did not. Participants rated the female speaker significantly lower than the male speaker, but only when the speaker was disfluent. These results are explained through the lens of attributional gender bias.